Adhesive free-standing multilayer films containing sulfated levan for biomedical applications. (15th March 2018) - Gomes, Tiago D.; Caridade, Sofia G.; Sousa, Maria P.; Azevedo, Sara; Kandur, Muhammed Y.; Öner, Ebru T.; Alves, Natália M.; Mano, João F.
Graphical abstract: Sulfated Levan (L-S) was introduced on the chitosan (CHI)/alginate (ALG) system. The presence of L-S lead to an adhesion strength 4 times higher than the control (CHI/ALG) multilayered films. Moreover, such free-standing membranes were myoconductive even in the absence of crosslinking. Abstract: This work is the first reporting the use of layer-by-layer to produce adhesive free-standing (FS) films fully produced using natural-based macromolecules: chitosan (CHI), alginate (ALG) and sulfated levan (L-S). The deposition conditions of the natural polymers were studied through zeta potential measurements and quartz crystal microbalance with dissipation monitoring analysis. The properties of the FS films were evaluated and compared with the control ones composed of only CHI and ALG in order to assess the influence of levan polysaccharide introduced in the multilayers. Tensile tests, dynamic mechanical analysis and single lap shear strength tests were performed to evaluate the mechanical properties of the prepared FS films. The presence of L-S conferred both higher tensile strength and shear strength to the developed FS membranes. The results showed an adhesion strength 4 times higher than the control (CHI/ALG) FS films demonstrating the adhesive character of the FS films containing L-S. Morphological and topography studies were carried out revealing that the crosslinking reaction granted the L-S based FS film with a higher roughness and surface homogeneity. Preliminary biological assays were performed by cultivating myoblasts cells on the surface of the produced FS films. Both crosslinked and uncrosslinked FS films containing L-S were cytocompatible and myoconductive. Statement of Significance: Sutures remain as the "gold standard" for wound closure and bleeding control; however they still have limitations such as, high infection rate, inconvenience in handling, and concern over possible transmission of blood-borne disease through the use of needles. One of the challenges of tissue engineering consist on the design and development of biocompatible tissue adhesives and sealants with high adhesion properties to repair or attach devices to tissues. In this work, the introduction of sulfated levan (L-S) on multilayered free-standing membranes was proposed to confer adhesive properties. Moreover, the films were myoconductive even in the absence of crosslinking just by the presence of L-S. This study provides a promising strategy to develop biological adhesives and for cardiac tissue engineering applications.